A photocatalyst for reducing low-concentration carbon dioxide and a preparation method thereof
By introducing nickel and aluminum into the photocatalyst, forming a hollow multi-stage CoNiAl-LDHs structure, the problem of insufficient CO2 adsorption and electron-hole separation capabilities of existing photocatalysts in low-concentration carbon dioxide environments is solved, and efficient CO2 reduction is achieved Performance improvement.
Patent Information
- Application Number
- CN202311271891.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing photocatalysts exhibit lower CO2 adsorption efficiency and product generation rate in low concentration carbon dioxide environments, and layered bimetallic hydroxides (LDHs) are at CO2 adsorption activation, electron-hole separation and surface catalytic active sites. There is room for improvement in terms of aspects, mainly due to the strong interaction between layers, the light absorption capacity is weak, electrons are prone to recombination with holes, and the active sites cannot be fully exposed.
Using rhombic dodecahedral Co-metal organic frame (ZIF-67) as template, nickel and aluminum are introduced through self-etching method to form a hollow multi-stage CoNiAl-LDHs photocatalyst, and its electronic structure and energy band structure are adjusted to improve CO2 adsorption activation and photocatalytic rate.
It significantly improves the adsorption activation and photocatalytic rate of CO2, improves the activity and selectivity of CO2 conversion into CO, and has a simple preparation method and low cost, which is suitable for mass production.
Smart Images

Figure CN117225420B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a photocatalyst for reducing low-concentration carbon dioxide and a preparation method thereof. Background Art
[0002] Photocatalytic CO2 reduction technology is considered to be a potential key technology for realizing CO2 resource utilization and developing new solar clean energy. Photocatalytic CO2 reduction is the use of semiconductor photocatalysts to convert CO2 and water into energy substances (such as CO, CH3OH, CH4, etc.), which is one of the ideal solutions to the sustainable solution of global warming and energy crisis. However, CO2 is an inert molecule, and the dissociation energy of the C=O bond can be as high as ~750kJ mol -1 ; In addition, the photoreduction of CO2 is a multi-electron transfer proton coupling process with low product selectivity and generation rate. Therefore, designing and synthesizing a photocatalyst that can efficiently split water and reduce CO2 is a necessary condition to meet this challenge.
[0003] So far, various photocatalysts for the efficient conversion of CO2 have been reported, however, most of these studies were conducted in a pure CO2 atmosphere. Given the low concentration of CO2 in the atmosphere, it is worth exploring low-concentration CO2 conversion schemes. In addition, since the electron-hole pairs generated by photoexcitation are very easy to recombine, the product generation rate is low. Therefore, improving the adsorption efficiency of CO2 and adjusting the band structure of semiconductor catalysts to promote electron-hole separation are the key to solving this problem.
[0004] Layered materials usually have a high specific surface area and relatively abundant active sites involved in catalytic reactions. Among layered materials, layered double hydroxides (LDHs) are two-dimensional layered anion materials with a brucite structure. The main layer is composed of divalent and trivalent metal ion hydroxides that are highly dispersed and covalently bonded, and are rich in positive charges; the interlayer anions are arranged in an orderly manner, and the charge of the main layer is balanced by electrostatic forces, and the two are arranged in an orderly manner. On the one hand, LDHs has the characteristics of adjustable metal cations in the main layer and exchangeable anions in the interlayer, so its band structure as a photocatalyst is easier to control, and can be applied to different photocatalytic fields; on the other hand, the basic hydroxyl group of LDHs is conducive to the adsorption of CO2 and also helps to activate inert CO2 molecules.
[0005] Although the existing technology has conducted extensive research on LDHs photocatalysts, the LDHs reported earlier still have a lot of room for improvement in CO2 adsorption activation, electron-hole separation and migration, and surface catalytic active sites. The main reason is that the strong interaction between LDHs layers leads to stacking or aggregation, resulting in weak light absorption ability, easy recombination of photogenerated electrons in the bulk phase with holes, and insufficient exposure of active sites, which seriously restricts the improvement of photocatalytic performance and subsequent applications. Therefore, how to obtain LDHs photocatalytic materials with strong CO2 absorption, strong electron-hole separation ability, good stability and actual CO2 conversion potential is still the current research focus. Summary of the invention
[0006] The object of the present invention is to provide a photocatalyst for reducing low-concentration carbon dioxide and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art, thereby ensuring high activity and high selectivity of CO2 reduction to CO.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention is to provide a method for preparing a hollow multi-level CoNiAl-LDHs photocatalyst, comprising: using a rhombic dodecahedron Co-metal organic framework (ZIF-67) as a template to self-etch and introduce Ni and Al to form a hollow multi-level CoNiAl-LDHs photocatalyst.
[0009] Preferably, the preparation method comprises the following steps:
[0010] (1) dissolving a cobalt source and dimethylimidazole in an organic solvent to obtain a solution A, reacting, and obtaining a precipitate, namely the rhombic dodecahedron Co-metal organic framework;
[0011] (2) dissolving a nickel source and an aluminum source in an organic solvent, and then mixing the solution with the rhombic dodecahedron Co-metal organic framework to obtain a solution B, and reacting the solution to obtain a precipitate, namely the hollow multi-level CoNiAl-LDHs photocatalyst.
[0012] The self-etching template of the present invention must use Co as the metal center, otherwise the rhombic dodecahedron cannot be formed. In addition, a certain proportion of nickel must be introduced during the self-etching process of the present invention. If only Al is introduced, LDHs cannot be grown on the template.
[0013] More preferably, the organic solvent in step (1) is methanol, and the organic solvent in step (2) is ethanol.
[0014] More preferably, in the solution A, the concentration of the cobalt source is 0.001 to 1 mol·L -1The concentration of dimethylimidazole is 0.001 to 1 mol·L -1 .
[0015] More preferably, the reaction temperature in step (1) is 25 to 200° C. and the reaction time is 8 to 36 hours.
[0016] More preferably, in the solution B, the molar ratio of the rhombic dodecahedron Co-MOF, the nickel source and the aluminum source is 1-9:1-9:1-9, and the total metal ion concentration is 0.001-1 mol·L -1 .
[0017] More preferably, the ratio of the molar amount of the aluminum source to the total molar amount does not exceed 10%.
[0018] More preferably, the reaction temperature in step (2) is 25 to 200° C. and the reaction time is 0.5 to 10 h.
[0019] More preferably, the cobalt source is cobalt nitrate, the nickel source is nickel nitrate, and the aluminum source is aluminum nitrate.
[0020] The second technical solution of the present invention is to provide a hollow multi-stage CoNiAl-LDHs photocatalyst obtained according to the above preparation method.
[0021] The third technical solution of the present invention is to provide an application of the above-mentioned hollow multi-stage CoNiAl-LDHs photocatalyst in the photocatalytic reduction of low-concentration CO2.
[0022] Preferably, in the photocatalytic CO2 reduction reaction, the volume fraction of CO2 is 10%.
[0023] Considering the Lewis acidity of CO2, alkaline catalysts are beneficial to the adsorption and activation of CO2.
[0024] Technical principle: The present invention provides a hollow multi-level CoNiAl-LDHs photocatalyst and a preparation method thereof. The morphology of the material is a hollow multi-level nanoflower structure composed of nanosheets. With the introduction of the Al element, the electronic structure and band structure of the product change significantly, enhancing the reaction activity; at the same time, the hollow multi-level CoNiAl-LDHs photocatalyst has a larger specific surface area than the LDHs prepared by the traditional hydrothermal method, which can significantly improve the corresponding CO2 enrichment capacity, thereby enhancing the adsorption and activation of CO2 and improving the photocatalytic rate. Therefore, the catalytic material is used for the photocatalytic reduction of low-concentration CO2 (10% CO2 / Ar) to generate CO with high yield and high selectivity.
[0025] By introducing relatively inert Al, the valence state of Ni at the active site is fundamentally regulated, thereby improving the selectivity for carbon monoxide.
[0026] The beneficial technical effects of the present invention are as follows:
[0027] The present invention uses rhombic dodecahedron ZIF-67 as a template, introduces Ni and Al by self-etching method, and constructs a hollow multi-level CoNiAl-LDHs nanoflower-shaped photocatalyst containing different electronic states. Compared with CoNi-LDHs, in terms of photocatalytic performance, the introduction of Al adjusts the electronic structure of the catalyst, reduces the band gap width, thereby accelerating the separation of photogenerated charges and holes, improves the utilization rate of photogenerated carriers, and significantly improves the activity and selectivity of photocatalytic CO2 conversion to CO; in terms of production and application, the preparation method of the present invention is simple and novel, the synthesis cost is low, it is easy to mass produce, and has good application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the X-ray powder diffraction pattern of the CoNiAl-LDHs photocatalyst in Example 1.
[0029] Figure 2 This is the X-ray powder diffraction pattern of the CoNi-LDHs photocatalyst in Example 2.
[0030] Figure 3 This is a scanning electron microscope image of ZIF-67 in Example 1.
[0031] Figure 4 This is a scanning electron microscope image of the CoNiAl-LDHs photocatalyst in Example 1.
[0032] Figure 5 This is a scanning electron microscope image of the CoNi-LDHs photocatalyst in Example 2.
[0033] Figure 6 This is a scanning electron microscope image of the CoNiAl-LDHs-a photocatalyst in Example 3.
[0034] Figure 7 This is a scanning electron microscope image of the CoNiAl-LDHs-b photocatalyst in Example 4.
[0035] Figure 8 This is a scanning electron microscope image of the CoNiAl-LDHs-c photocatalyst in Example 5.
[0036] Fig. 9 Solid ultraviolet diffuse reflectance spectra of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2.
[0037] Fig.10Tauc plots of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2.
[0038] Fig.11 1 and 2 are Mott-Schottky plots of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2.
[0039] Fig.12 Schematic diagram of the energy band structure of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2.
[0040] Fig.13 The Ni 2p X-ray photoelectron spectra of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2 are shown.
[0041] Fig.14 2p X-ray photoelectron spectra of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2.
[0042] Fig.15 This is a diagram showing the catalytic performance of the CoNiAl-LDHs photocatalyst in Example 1 for catalytic reduction of low concentration carbon dioxide to carbon monoxide.
[0043] Fig.16 This is a diagram showing the catalytic performance of the CoNi-LDHs photocatalyst in Example 2 for catalytic reduction of low concentration carbon dioxide to carbon monoxide.
[0044] Fig.17 This is a diagram showing the catalytic performance of the CoNiAl-LDHs-c photocatalyst in Example 5 for catalytic reduction of low concentration carbon dioxide to carbon monoxide.
[0045] Fig.18 Graph showing the selectivity of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2 for catalyzing the reduction of carbon dioxide to carbon monoxide. DETAILED DESCRIPTION
[0046] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0047] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0048] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the invention.
[0049] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.
[0050] The "room temperature" described in the present invention is 25°C unless otherwise specified.
[0051] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.
[0052] Example 1
[0053] Preparation of CoNiAl-LDHs photocatalyst:
[0054] (1) Weigh 1.45 g of cobalt nitrate and dissolve it in 125 mL of methanol, and stir it to obtain solution 1; weigh 1.64 g of dimethylimidazole and dissolve it in 125 mL of methanol, and stir it to obtain solution 2; quickly add solution 1 to solution 2 to obtain a mixed solution; in the mixed solution, the concentration of cobalt nitrate is 0.02 mol·L -1 , dimethylimidazole concentration is 0.08 mol·L -1 The mixed solution was allowed to stand at room temperature for 24 h, centrifuged, washed with methanol, and dried to obtain ZIF-67 (rhombic dodecahedron).
[0055] (2) Weigh 50 mg of ZIF-67 in 12.5 mL of ethanol to form suspension solution 3; weigh 115.7 mg of nickel nitrate and 16.6 mg of aluminum nitrate and dissolve them in 37.5 mL of ethanol by ultrasonication to form solution solution 4; slowly add solution solution 4 to suspension solution 3 under stirring at room temperature to obtain a precursor solution; the concentration of ZIF-67 in the precursor solution is 0.002 mol·L -1 , the concentration of nickel nitrate is 0.007 mol·L -1 , aluminum nitrate concentration is 0.001 mol·L -1The precursor solution was stirred at room temperature for 1 hour, washed by centrifugation with ethanol, and dried to obtain the CoNiAl-LDHs photocatalyst.
[0056] Figure 1 This is the X-ray powder diffraction pattern of the CoNiAl-LDHs photocatalyst in Example 1. Figure 3 This is a scanning electron microscope image of ZIF-67 in Example 1. Figure 4 This is a scanning electron microscope image of the CoNiAl-LDHs photocatalyst in Example 1.
[0057] Example 2 (replacing aluminum nitrate with an equimolar amount of nickel nitrate)
[0058] Preparation of CoNi-LDHs photocatalyst:
[0059] (1) Weigh 1.45 g of cobalt nitrate and dissolve it in 125 mL of methanol, and stir it to obtain solution 1; weigh 1.64 g of dimethylimidazole and dissolve it in 125 mL of methanol, and stir it to obtain solution 2; quickly add solution 1 to solution 2 to obtain a mixed solution; in the mixed solution, the concentration of cobalt nitrate is 0.02 mol·L -1 , dimethylimidazole concentration is 0.08 mol·L -1 The mixed solution was allowed to stand at room temperature for 24 h, centrifuged, washed with methanol, and dried to obtain ZIF-67.
[0060] (2) Weigh 50 mg of ZIF-67 in 12.5 mL of ethanol to form suspension 3; weigh 128.5 mg of nickel nitrate and dissolve it in 37.5 mL of ethanol by ultrasonication to form solution 4; slowly add solution 4 to suspension 3 under stirring at room temperature to obtain a precursor solution; the concentration of ZIF-67 in the precursor solution is 0.002 mol·L -1 , the concentration of nickel nitrate is 0.009 mol·L -1 The precursor solution was stirred at room temperature for 1 hour, washed by centrifugation with ethanol, and dried to obtain the CoNi-LDHs photocatalyst.
[0061] Figure 2 This is the X-ray powder diffraction pattern of the CoNi-LDHs photocatalyst in Example 2. Figure 5 This is a scanning electron microscope image of the CoNi-LDHs photocatalyst in Example 2.
[0062] Depend on Figure 4 , Figure 5 It can be seen that the difference in microscopic morphology between the products of Example 1 and Example 2 of the present invention is small, which is mainly due to the lower amount of Al introduced in Example 1; when the amount of Al introduced is less than 10% of the total molar amount, it is not enough to have a significant impact on the microscopic morphology of the product.
[0063] Example 3 (increase in the amount of aluminum nitrate introduced)
[0064] Preparation of CoNiAl-LDHs-a photocatalyst:
[0065] (1) Weigh 1.45 g of cobalt nitrate and dissolve it in 125 mL of methanol, and stir it to obtain solution 1; weigh 1.64 g of dimethylimidazole and dissolve it in 125 mL of methanol, and stir it to obtain solution 2; quickly add solution 1 to solution 2 to obtain a mixed solution; in the mixed solution, the concentration of cobalt nitrate is 0.02 mol·L -1 , dimethylimidazole concentration is 0.08 mol·L -1 The mixed solution was allowed to stand at room temperature for 24 h, centrifuged, washed with methanol, and dried to obtain ZIF-67.
[0066] (2) Weigh 50 mg of ZIF-67 in 12.5 mL of ethanol to form suspension 3; weigh 115.7 mg of nickel nitrate and 33 mg of aluminum nitrate and dissolve them in 37.5 mL of ethanol by ultrasonication to form solution 4; slowly add solution 4 to suspension 3 under stirring at room temperature to obtain a precursor solution; the concentration of ZIF-67 in the precursor solution is 0.002 mol·L -1 , the concentration of nickel nitrate is 0.007 mol·L -1 , aluminum nitrate concentration is 0.002 mol·L -1 The precursor solution was stirred at room temperature for 1 hour, washed by centrifugation with ethanol, and dried to obtain the CoNiAl-LDHs photocatalyst.
[0067] Figure 6 This is a scanning electron microscope image of the CoNiAl-LDHs-a photocatalyst in Example 3.
[0068] like Figure 6 As shown in the figure, when the amount of Al introduced exceeds 10%, only the LDHs sheet structure is formed, and the hollow structure cannot be formed. In addition, the performance improvement of the CoNiAl-LDHs photocatalyst is mainly related to the introduction of a small amount of Al to change the electronic properties and band structure of the active site. Therefore, the present invention is different from other solutions that optimize performance by morphology.
[0069] Example 4 (Increase in reaction temperature during self-etching process)
[0070] Preparation of CoNiAl-LDHs-b photocatalyst:
[0071] (1) Weigh 1.45 g of cobalt nitrate and dissolve it in 125 mL of methanol, and stir it to obtain solution 1; weigh 1.64 g of dimethylimidazole and dissolve it in 125 mL of methanol, and stir it to obtain solution 2; quickly add solution 1 to solution 2 to obtain a mixed solution; in the mixed solution, the concentration of cobalt nitrate is 0.02 mol·L -1 , dimethylimidazole concentration is 0.08 mol·L -1 The mixed solution was allowed to stand at room temperature for 24 h, centrifuged, washed with methanol, and dried to obtain ZIF-67.
[0072] (2) Weigh 50 mg of ZIF-67 in 12.5 mL of ethanol to form suspension 3; weigh 115.7 mg of nickel nitrate and 16.6 mg of aluminum nitrate and dissolve them in 37.5 mL of ethanol by ultrasonication to form solution 4; slowly add solution 4 to suspension 3 under stirring at 80° C. to obtain a precursor solution; the concentration of ZIF-67 in the precursor solution is 0.002 mol·L -1 , the concentration of nickel nitrate is 0.007 mol·L -1 , aluminum nitrate concentration is 0.001 mol·L -1 The precursor solution was stirred at 80°C for 1 hour, washed by centrifugation with ethanol, and dried to obtain the CoNiAl-LDHs-b photocatalyst.
[0073] Figure 7 is a scanning electron microscope image of the CoNiAl-LDHs-b photocatalyst in Example 4. Figure 7 As shown in the figure, when the reaction temperature is raised to 80°C during the self-etching process, the product morphology is still an LDHs flake structure and a hollow structure cannot be formed; this is because when the reaction temperature increases, the metal organic ligand bond breaking rate and the LDHs formation rate are accelerated.
[0074] Example 5 (Hydrothermal method)
[0075] Preparation of CoNiAl-LDHs-c photocatalyst:
[0076] Weigh 2.62g of cobalt nitrate, 2.62g of nickel nitrate, 2.25g of aluminum nitrate, and 5.4g of urea and dissolve them in 300mL of water. The concentration of cobalt nitrate and nickel nitrate in the mixed solution is 0.03mol·L -1 , aluminum nitrate concentration is 0.02 mol·L -1 After stirring for 10 min, the mixture was transferred to a hydrothermal reactor and aged at 120 °C for 12 h. The mixture was centrifuged, washed with deionized water, and dried to obtain CoNiAl-LDHs-c.
[0077] Figure 8 is a scanning electron microscope image of the CoNiAl-LDHs-c photocatalyst in Example 5. Figure 8 As shown, the LDHs formed by the traditional hydrothermal method have a sheet-like structure with a relatively small surface area and low CO2 adsorption capacity.
[0078] Fig. 9 The solid ultraviolet diffuse reflectance spectra of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2 are shown in FIG. Fig. 9 It can be seen that the light absorption intensity of CoNiAl-LDHs photocatalyst is significantly higher than that of CoNi-LDHs photocatalyst.
[0079] Fig.10 Tauc plots of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2. Fig.10 It shows that after the introduction of Al, the band gap width decreases from 1.79eV to 1.75eV, indicating that the introduction of Al changes the band structure of LDHs.
[0080] Fig.11 1 and 2 are Mott-Schottky plots of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2. Fig.11 The flat band potentials of CoNiAl-LDHs photocatalyst and CoNi-LDHs photocatalyst were measured to be -0.66 and -0.83 eV (relative to saturated Ag / AgCl electrode), respectively.
[0081] Fig.12 Schematic diagram of the energy band structure of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2. As shown in the figure, after the introduction of Al, the energy band structure of the catalyst is adjusted, and the band gap width is reduced (from Eg = E CB -E VB Therefore, the separation and migration of photogenerated electrons and holes in the CoNiAl-LDHs photocatalyst after the introduction of Al is significantly changed compared with that in the CoNi-LDHs photocatalyst, which is more conducive to the electron transition to the conduction band and then participate in the CO2 reduction reaction.
[0082] Fig.13 The Ni 2p X-ray photoelectron spectra of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2 are shown.
[0083] Fig.14 2p X-ray photoelectron spectra of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2.
[0084] like Fig.13, Fig.14 As shown, the introduction of Al has no obvious effect on the electronic state of Co, but it can change the valence state of Ni from positive divalent and positive trivalent to positive divalent, thus adjusting the electronic state of Ni.
[0085] Effect verification
[0086] (1) The performance of the photocatalysts of Examples 1, 2, and 5 was tested. The specific test method is: weigh 10 mg of the photocatalyst in 100 μL of deionized water, and then spread it in a 50 mL offline photocatalytic reactor. Use 10% carbon dioxide (10% CO2 / Ar) as the reaction atmosphere, illuminate with a 300W xenon lamp at normal pressure, take samples at regular intervals, and analyze the results with gas chromatography; after the reaction is completed, test the selectivity of carbon dioxide reduction to carbon monoxide. The test results are as follows: Figure 15-18 shown.
[0087] Fig.15 This is a diagram showing the catalytic performance of the CoNiAl-LDHs photocatalyst in Example 1 for catalytic reduction of low concentration carbon dioxide to carbon monoxide.
[0088] Fig.16 This is a diagram showing the catalytic performance of the CoNi-LDHs photocatalyst in Example 2 for catalytic reduction of low concentration carbon dioxide to carbon monoxide.
[0089] Fig.17 This is a diagram showing the catalytic performance of the CoNiAl-LDHs-c photocatalyst in Example 5 for catalytic reduction of low concentration carbon dioxide to carbon monoxide.
[0090] Depend on Figure 15-17 As shown in the figure, due to the regulation of Al on the electronic structure of Ni, the performance of CoNiAl-LDHs photocatalyst to produce CO from low concentration CO2 is much higher than that of CoNi-LDHs photocatalyst; at the same time, due to its hollow structure, the specific surface area is much higher than that of the flaky CoNiAl-LDHs-c prepared by the traditional hydrothermal method. Therefore, the performance of CoNiAl-LDHs photocatalyst to produce CO from low concentration CO2 is also higher than that of CoNiAl-LDHs-c photocatalyst.
[0091] Fig.18 The selectivity diagram of the CoNiAl-LDHs photocatalyst in Example 1 and the CoNi-LDHs photocatalyst in Example 2 for catalyzing the reduction of carbon dioxide to carbon monoxide. Fig.18It can be seen that the selectivity of CoNiAl-LDHs photocatalyst for carbon monoxide is 100%. This is mainly because the introduction of Al adjusts the electronic structure of Ni at the active site, reduces the adsorption energy of the key intermediate *CO at the active site, and makes *CO easily desorbed to form CO; while CoNi-LDHs photocatalyst has a strong adsorption of the key intermediate *CO, resulting in some *CO being strongly adsorbed at the active site and continuing to be hydrogenated to form byproduct CH4.
[0092] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a hollow multi-stage CoNiAl-LDHs photocatalyst for photocatalytic reduction of low-concentration CO2, characterized in that: include: The rhombic dodecahedral Co-metal organic framework was used as a template for self-etching to introduce Ni and Al to form a hollow multi-level CoNiAl-LDHs photocatalyst. The preparation method comprises the following steps: (1) dissolving a cobalt source and dimethylimidazole in an organic solvent to obtain a solution A, reacting, and obtaining a precipitate, namely the rhombic dodecahedron Co-metal organic framework; (2) dissolving a nickel source and an aluminum source in an organic solvent, and then mixing the solution with the rhombic dodecahedron Co-metal organic framework to obtain a solution B, reacting the solution at room temperature for 0.5 to 10 h, and obtaining a precipitate, which is the hollow multi-level CoNiAl-LDHs photocatalyst; In the solution B, the molar ratio of the rhombic dodecahedron Co-metal organic framework, the nickel source and the aluminum source is 2:7:1, and the total concentration of metal ions is 0.001-1 mol·L -1 .
2. The preparation method according to claim 1, characterized in that: In the solution A, the concentration of the cobalt source is 0.001~1 mol·L -1 The concentration of dimethylimidazole is 0.001~1 mol·L -1 .
3. The preparation method according to claim 1, characterized in that: The reaction temperature in step (1) is 25-200°C and the reaction time is 8-36 h.
4. The preparation method according to claim 1, characterized in that: The cobalt source is cobalt nitrate, the nickel source is nickel nitrate, and the aluminum source is aluminum nitrate.
5. A hollow multi-level CoNiAl-LDHs photocatalyst obtained according to the preparation method according to any one of claims 1 to 4.
6. Use of the hollow multi-stage CoNiAl-LDHs photocatalyst according to claim 5 in photocatalytic reduction of low-concentration CO2.
7. The use according to claim 6, characterized in that: In the photocatalytic CO2 reduction reaction, the volume fraction of CO2 is 10%.
